CircRNA circ_POLA2 Promotes Cervical Squamous Cell Carcinoma Progression via Regulating miR-326/GNB1 - Cao, Yuan; Li, Juan; Jia, Yanyan; Zhang, Ruitao; Shi, Huirong (Frontiers in Oncology, 2020)
Circular RNAs (CircRNAs) are a group of non-coding RNAs that have essential function in the development and progression of various cancers. The expression pattern and function of circRNA in cervical squamous cell carcinoma (CESC) is not fully understood.In the present study, we aimed to investigate the expression profiles and regulation mechanism of circRNA circ_POLA2 in CESC. Circ_POLA2 was highly expressed in CESC tissues and positively correlated with poor prognosis in CESC patients.Knockdown of circ_POLA2 using shRNA inhibited cervical cancer cell proliferation, migration and invasion both in vitro and in vivo. Mechanistically, circ_POLA2 was identified to function as a ceRNA by sponging microRNA-326 (miR-326). Furthermore, miR-326 negatively regulated G protein subunit Beta 1 (GNB1) by targeting its 3'-UTR.Intriguingly, we found that GNB1 was overexpressed and associated with poor prognosis in CESC patients. Overexpression GNB1 could antagonize the inhibitory effect of miR-326 on cervical cancer cell proliferation, migration and invasion. In addition, we demonstrated that circ_POLA2/miR-326/GNB1 axis regulated ERK signaling. In conclusion, circ_POLA2 promotes cervical squamous cell carcinoma development and progression via regulating miR-326/GNB1, which might serve a novel therapeutic target for CESC patients.